Gadgetku.id application as a Solution to Facilitate the Fulfillment of All Gadget Needs today (case study: area Tangerang Banten) - Sutrisno, Sutrisno; Sajidin, Ahmad (Pandawan, 2019)
The gadget is a sophisticated item that can present a variety of news media, socialnetworking, hobbies, and even entertainment. The presence of gadgets today makes somepeople become dependent. If the gadget is damaged, they will repair the gadget itself or bringit to the service place. The problem in this study is the difficulty of finding information about theplace of seller of gadget components and looking for a trusted service place, the nearestlocation and affordable prices. To overcome this problem, the author designed an applicationcalled Gadgetku.Id used a qualitative research method consisting of data collection, dataanalysis and system design. In this application have 2 main services, namely service andshop. The purpose of designing this application is to be able to assist users in finding a trustedservice place, the nearest location, safe, scheduled and without the need to go to the serviceplace and help to find gadget needs through the shop feature.